2014
DOI: 10.1080/09692290.2014.915578
|View full text |Cite
|
Sign up to set email alerts
|

Brave New World? Macro-prudential policy and the new political economy of the federal reserve

Abstract: The Financial Crisis that started in 2007 ushered in new responsibilities for central banks, particularly for what is termed "macro-prudential policy," or MPP. The goal of this policy is to monitor and contain overall risk in the financial sector. Implementing MPP, however, carries the potential for distributional conflict with the largest financial firms and the politicization of central bank policy. In light of this risk, this essay analyses the institutional implications of MPP for a leading central bank, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 54 publications
1
23
0
1
Order By: Relevance
“…In the euro area, "net trust" in the European Central Bank fell from +29 to -23 in the six years following 2008, meaning that a majority distrusted the ECB in 2014 (Roth et al 2016). In light of these developments, some authors have observed a "legitimacy crisis of money" (Weber 2016), while others have diagnosed a "legitimacy problem" for the Fed (Goodhart 2015;Jacobs/King 2016: 31) and failures of output and throughput legitimacy for the ECB (Scharpf 2012: 21;Schmidt 2016). There is little understanding, however, of how these two developments relate to each other.…”
Section: Introductionmentioning
confidence: 99%
“…In the euro area, "net trust" in the European Central Bank fell from +29 to -23 in the six years following 2008, meaning that a majority distrusted the ECB in 2014 (Roth et al 2016). In light of these developments, some authors have observed a "legitimacy crisis of money" (Weber 2016), while others have diagnosed a "legitimacy problem" for the Fed (Goodhart 2015;Jacobs/King 2016: 31) and failures of output and throughput legitimacy for the ECB (Scharpf 2012: 21;Schmidt 2016). There is little understanding, however, of how these two developments relate to each other.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing these two variables into our accounts of persuasive struggle and ideational change enables us to deepen our understanding of the dynamics of ideational change at times of crisis. This is important and relevant for our understanding of the political economy of the recent financial crash, because a quite rapid and radical intellectual change has been evident in the field of financial regulation in the form of an embrace of a macroprudential frame (Borio, 2009, Baker 2013a, Goodhart, 2014. In contrast in the field of macroeconomic policy -both monetary and fiscal policy, many pre-crash beliefs remain prominent, there is evidence of ideational stickiness and inertia, and despite some policy experimentation, overarching policy frameworks and their rationales have not as yet been overhauled (Farrell and Quiggin, 2012, Blyth, 2013aDellepiane-Avellaneda, 2014, Hodson and Mabbett, 2010, Clift, 2014.…”
Section: Varieties Of Economic Crisis Varieties Of Ideationalmentioning
confidence: 99%
“…It is now widely acknowledged by academics and policy makers that a macroprudential ideational shift emerged from the financial crash of 2008 (Borio, 2009, Baker, 2013a, Persaud, 2010, Haldane, 2009, Datz, 2013, Goodhart, 2014, Hanson, Kyap and Stein, 2011 denying that individually rational self-interested investment strategies are likely to produce financial stability and equilibrium, identifying finance's inherent procyclical tendencies, the propensity for herd behaviour amongst investors and the destabilising effects of financial complexity (Borio, 2009, Baker, 2013b. The macroprudential ideational shift through its assumptions about the behaviour and properties of financial markets, justifies a regulator intervening with countercyclical policy measures to restrain and direct market activities on a system wide basis.…”
Section: The Macroprudential Third Order Ideational Shift Of 2009mentioning
confidence: 99%
“…Baker (2013: 133), who describes this shift as 'a potential trajectory change in financial regulation', emphasizes that it is 'still in its infancy and so does not yet look conspicuously different from the previous status quo'. (Less sanguine observers do not expect it to: Goodhart (2014), among others, severely doubts the ability of the Federal Reserve, with no macroprudential analogue to open-market operations and no monopoly control over the policy instruments of macroprudentialism, to deliver on the expectations enshrined in DoddFrank. ) Third, it is, as Mügge (2014) has claimed, very difficult to assess the efficacy of financial reforms, or even to ascertain what reforms are necessary, while the effects of the 'unconventional' monetary policy of quantitative easing -only recently shuttered in the USA, and seemingly now set for activation in the Euro area -persist.…”
Section: Back To the Futurementioning
confidence: 91%